The quest for a philosophical YHWH (part 2) : philosophical criticism as exegetical methodology - Gericke, Jaco (Old Testament essays, 2006)
This is the second article in the series designated 'The quest for a philosophical YHWH'. In the first article, the main focus was on pioneering the possibility of philosophical-critical analysis by justifying the plea for the utilisation of philosophy of religion as auxiliary discipline in biblical studies. In this article, the primary concern lies with providing some introductory thoughts on the exegetical component of philosophical-critical analysis, i.e. philosophical-criticism a new form of biblical criticism. In this type of exegesis the practitioner attempts the identification, abstraction and reconstruction of the ontological, metaphysical, moral, theological, epistemological and other assumptions in the biblical discourse so as to examine and discuss the philosophical questions these assumptions give rise to in their relation to one or more of the loci on the agenda of philosophy of religion.